Diseño del sistema SCADA en las estaciones de bombeo y tanques de reserva de agua potable en la ciudad de Loja. - Tapia Ramírez, Eduardo Franco (2011)
Monitoring System Control and Data Acquisition SCADA is applied to the 22 pumping stations with their respective units operating reserve account in Municipal Unit Water and Sewer UMAPAL Loja. At present the UMAPAL not have a communication system that supports SCADA applications, however the trend is aimed at automating the distribution system of drinking water, which is essential to have SCADA systems pumping stations and tanks reserve. This paper shows the process involved in the Supervision Control and Data Acquisition of the 22 pumping stations with their reserve units, which covers the design of communications between the remote stations (Pump Stations and Tanks Reserve) with the Control Center, and by DSC Module LabVIEW Datalogging and Supervisory Contro, develops the GUI. We propose a wireless communication solution between the pumping stations, tanks Book Control Center that has a data capacity for a SCADA system. It should be stressed that allows communication solution raised to provide a means of monitoring and control instrumentation operations staff, assisting with reliable information about the operating conditions of the pumping stations and storage tanks in the city of Loja. They carry out the phases of the design according to the sequence of lower to upper levels of the pyramid in a Reference Model CIM systems automation. In addition, for the study of links, use the Radio Mobile software, it allows us to verify the existence of lines of sight between each link, determining the loss, gain profiles and determine the characteristics of each of the links between the tower Multipoint and remote stations. We present simulation and the results of each of the links, which guarantees the proper functioning of the network. Graphical interface is made known SCADApump, which simulates the actual operation of the state of operation and exchange of information between remote stations and the Control Center. Then, the graphical interface was developed for the prototype that denomina SCADAdemo, which consists of a pumping station with their respective Reserve unit, which checks the exchange of information between a computer is the server localy another computer requesting services to the server, which is called a client. We present the economic and environmental assessment which analyzes the amount of investment generated by the project implementation, as well as recovery time of investment and the positive impact on the environment. Finally, some conclusions are made and recommendations obtained from the development of this project.